Business process change a business process management guide for managers and process professionals - Harmon, Paul 1942- (Elsevier, 2014)
Business Process Change, 3rd Edition provides a balanced view of the field of business process change. Bestselling author Paul Harmon offers concepts, methods, cases for all aspects and phases of successful business process improvement. Updated and added for this edition is new material on the development of business models and business process architecture development, on integrating decision management models and business rules, on service processes and on dynamic case management, and on integrating various approaches in a broad business process management approach. New to this edition: How to develop business models and business process architecture How to integrate decision management models and business rulesNew material on service processes and on dynamic case managementLearn to integrate various approaches in a broad business process management approachExtensive revision and update addresses Business Process Management Systems, and the integration of process redesign and Six SigmaLearn how all the different process elements fit together in this best first book on business process, now completely updated Tailor the presented methodology, which is based on best practices, to your organization's specific needs Understand the human aspects of process redesignBenefit from all new detailed case studies showing how these methods are implemented
Keywords: Commerce; Organizational Innovation; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Electronic commerce; Organizational change; System design; Prozessmanagement; Reengineering; Unternehmen; Organisationslehre; Änderung